Civil turbofan propulsion aerodynamics: thrust-Drag accounting and impact of engine installation position - Goulos, Ioannis; Otter, John J.; Tejero, Fernando; Hueso Rebassa, Josep; MacManus, David G. (Elsevier, 2021)
It is envisaged that the next generation of civil aero-engines will employ high bypass ratios to lower specific thrust and improve propulsive efficiency. This trend is likely to be accompanied with the integration of compact nacelle and exhausts in podded under-wing installation positions that are close coupled to the airframe. This leads to the requirement for a comprehensive methodology able to predict aerodynamic performance for combined airframe-engine architectures. This paper presents a novel thrust and drag accounting approach for the aerodynamic analysis of integrated airframe-engine systems. An integral metric is synthesised based on the concept of net vehicle force. This is accomplished through the consolidation of aerodynamic coefficients, combined with the engine cycle characteristics obtained from a thermodynamic matching model. The developed approach is coupled with an in-house tool for the aerodynamic design and analysis of installed aero-engines. This framework is deployed to quantify the impact of engine installation position on the aerodynamic performance of a future large turbofan installed on a commercial wide-body airframe. The governing flow mechanisms are identified and their influence is decomposed in terms of the impact on airframe, nacelle, and exhaust performance. It is shown that it is essential to include the impact of installation on the exhaust for the correct determination of overall airframe-engine performance. The difference in net vehicle force for a close coupled position can reach up to -0.70% of nominal standard net thrust relative to a representative baseline engine location.
Keywords: Aerospace engineering; Turbofan; Aerodynamics; Computational fluid dynamics; Thrust and drag accounting; Class-shape transformation